EVALUATION OF THE USE OF ANTI-NON STEROID INFLAMATION DRUGS ON GERIATRI - Karminingtyas, Sikni Retno; Oktianti, Dian; Furdiyanti, Nova Hasani; Sandriana, Mira; Kusuma, Arinda Maya (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2020)
Background: Geriatric patients differ from the general patient population. Geriatric differences with other populations include aspects of pharmacokinetics, pharmacodynamics, comorbidities, and the likelihood of adverse drug reactions (ADR). Objective: To determine the accuracy of the dosage and side effects of non-steroidal anti-inflammatory drugs (NSAIDs) in geriatric patients in the Inpatient Installation of Dr.Asmir Salatiga. Methods: The study was conducted non-experimental (observational), using descriptive methods and prospective data collection. Samples were 25 patients with total sampling method. Data analysis included drug use, dose accuracy and evaluation of drug side effects using the Naranjo algorithm. Results: Geriatric patients using the most non-steroidal anti-inflammatory drugs were 18 patients (72%). The largest group of non-steroidal anti-inflammatory drugs is the oxikam group of 12 patients (48%). The exact dosage of non-steroidal anti-inflammatory drugs is 19 cases (76%) on the right dose. Evaluation of drug side effects based on the Naranjo algorithm obtained scores for the